3, 6-Di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) catalysed metal-free amide bond formation from thioacids and amines at room temperature. Issue 35 (27th August 2020) - Samanta, Suvendu; Ray, Shounak; Bhaduri, Samanka Narayan; Samanta, Partha Kumar; Biswas, Papu
Graphical abstract: Highlights: Organocatalysis by 3, 6-Di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz). Amide bond formation from thioacids and amines. Metal-free mild reaction conditions. Wide range of aliphatic and aromatic amines as substrate. Abstract: A 3, 6-di(pyridin-2-yl)-1, 2, 4, 5-tetrazine (pytz) catalysed efficient, mild and metal-free method has been developed for direct amide bond synthesis from simple thioacids and amines as starting materials. This methodology is useful for aromatic, aliphatic, and heteroaromatic thioacids as well as primary, secondary, heterocyclic, and even functionalized amines. A wide substrates scope, operationally mild conditions, and acylation of amines without affecting other functional groups such as alcohols, esters, carbodithioates, among others make this strategy very attractive and practical.